Effectiveness Of State Tax Revenue In Reducing Poverty Rates In Indonesia - Cahyono, Heru; Suwitri, Sri; Agustina, Rina; Lituhayu, Dyah (Jurnal Mamangan, 2024)
Taxes are essential to the operation of the state because, in addition to serving as the primary source of funding, they serve a number of important purposes that promote communal welfare and development. Providing the state with the money it needs to pay various government and development initiatives is the primary goal of taxes. The state can fund social services, education, health care, and infrastructure development—all of which are critical to the welfare of the populace—through taxation. Taxes also serve as a tool for establishing social fairness. The state can provide advantages to the less fortunate and distribute income more fairly by collecting taxes from the wealthier citizens. This makes it easier for people at all levels of society to gain from progress and lessens social and economic inequalities. The findings demonstrated that state tax revenue's ability to lower poverty rates in Indonesia through health and education programs for the poor remains low, unequal, and insufficient for people who are currently poor or have low incomes. In terms of education, the dropout rate remains high, and rural communities continue to have inadequate access to health care. A comprehensive, integrated, and sustainable approach is required by the government in order to increase the impoverished population's access to health and education services in a way that is more sufficient, just, and equal